Cold compensators in apple tree ‘Golden Glory’: development and production - Soto Parra, Juan Manuel; Flores-cordova, Maria Antonia; Sánchez Chávez, Esteban; Pérez Leal, Ramona; Piña Ramírez, Francisco Javier (Revista Mexicana de Ciencias Agrícolas, 2020)
The apple tree (Malus domestica Borkh) is a temperate zone fruit tree that requires the application of sprouting promoters. The objective of this research was to study the efficiency of cold compensators: Erger, potassium nitrate, Thidiazuron (Revent), BroStart, Tecno Oil 100 EW and hydrogen peroxide, in the Golden Glory/MM 111 variety, the trees were planted in 2009, at 4 m between streets and 2 m between trees, (1 250 trees per ha), a factorial arrangement 56 bounded to 25 treatments with different concentrations was used using a Taguchi L25 structure generated by the Minitab 16.1.0.0 statistical package, in so much so that the statistical analysis was by means of response surface, weighing the effect of the factors to select those with the best effect in the production and development set. The variables evaluated were vegetative growth, node density, sprouting of one and two-year-old branches and production. The results obtained indicate that the treatments with Revent, potassium nitrate and Tecno Oil 100 EW oil had a positive effect on the variables of vegetative growth and production, the latter favored the increase with 90.7%. In knot density, Erger presented the best effect and in sprouting branches a year was BroStart in synergy with Revent and Erger. Finally, it is concluded that the compensators evaluated proved to be an alternative in dormancy breaking apple ‘Golden Glory’.